Incidence and prevalence of patellofemoral pain: a systematic review and meta-analysis - Smith, Benjamin E.; Selfe, James; Thacker, Damian; Hendrick, Paul; Bateman, Marcus; Moffatt, Fiona; Rathleff, Michael Skovdal; Smith, Toby O.; Logan, Pip (Public Library of Science, 2018)
Background: Patellofemoral pain is considered one of the most common forms of knee pain, affecting adults, adolescents, and physically active populations. Inconsistencies in reported incidence and prevalence exist and in relation to the allocation of healthcare and research funding, there is a clear need to accurately understand the epidemiology of patellofemoral pain.